Theatres in Roman Palestine and Provincia Arabia - Segal, Arthur. (Mnemosyne, Supplements, 1995)
This volume deals with the architectural history of the theatre in Roman Palestine and Provincia Arabia, a region which comprised a Jewish, Nabataean, and Hellenized population but lacked any tradition of classical theatre. The earliest examples, erected by Herod, were actually a foreign imposition upon the landscape of Judaea, while the theatres built in the Nabataean kingdom provided no more than an architectural setting for activities which were often unrelated to theatre in the accepted sense. When the Hellenized cities in the region began building their theatres, classical plays were already disappearing from the stage throughout the Roman world, their place taken by lighter, less select forms of public entertainment. The author then offers a comprehensive architectural analysis of each of the thirty theatres so far uncovered in the area. Richly illustrated, it provides a vivid reconstruction of a world which, though long gone, continues to fascinate.